The Effect of Infrastructure Development by The Ministry of Public Works and Public Housing on Regional Economic Growth - Reza, Mochammad Faizal; Indrijawati, Aini; Syarifuddin, Syarifuddin; Darmawati , Darmawati (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Economic disparities between regions in Indonesia necessitate an evaluation of the impact of infrastructure development as a catalyst for growth. This study analyzes the effect of infrastructure development by the Ministry of Public Works and Public Housing (PUPR) across four sectors—road construction, water resources, public works, and housing—on Indonesia’s regional economic growth. Using a quantitative explanatory approach, secondary data from 18 provinces (54 observations) were collected for 2022–2024. Data included PUPR’s budget realization and Regional Domestic Product (GRDP) at constant prices from the Central Statistics Agency. Multiple regression analysis assessed sectoral impacts. Road infrastructure significantly boosted regional economic growth (? = 0.573, p = 0.000), contributing 37.82% to growth variation. Water Resources (? = 0.158, p = 0.034) and Public Facilities (? = 0.189, p = 0.019) also showed positive effects, contributing 6.35% and 9.41%, respectively. Housing development had no significant impact (p = 0.792) and a negative partial effect (–2.18%). Collectively, the four sectors explained 51.4% of GRDP variance (R² = 0.514, F = 12.934, p = 0.000). Road, Water Resources, and Public Facilities infrastructure are pivotal for economic growth, while Housing policies require reevaluation. Findings advocate prioritizing high-impact sectors to foster inclusive and sustainable regional development.